Dunite solubilization kinetics in silicon-magnesium fertilization - Moretti, Luiz Gustavo [UNESP] (2021)
Dunite [(MgFe)2SiO4] is an igneous rock that remineralizes and corrects soil acidity as well as providing magnesium (Mg2+) and silicon (Si4+) to several crops of agricultural interest. However, few studies have verified its solubility in tropical soils, which is important for its use in different tropical conditions. In a greenhouse incubation experiment, this study verified the solubilization kinetics of dunite in clayey, medium texture, and sandy soils. The soil samples were dried and sieved (50 mesh), placed in plastic cups (300 g), and incubated for six months (at 60%–80% of the moisture retention capacity). Samples for pH (CaCl2 extractor), Mg2+ (resin extractor), and Si4+ (CaCl2 extractor) analysis were taken at 10, 20, 30, 40, 50, 60, 70, 85, 100, 115, 130, 150, and 180 days after incubation. The application of dunite led to an increase in Mg2+ and Si4+ contents and an acidity correction in the three studied soils. Its controlled release presents method for increasing the efficiency of magnesium fertilization. It allows for fewer losses due to Mg2+ leaching, as the dissolution kinetics are slower than soluble sources and have a residual effect for subsequent crops.